2020
DOI: 10.1111/apa.15609
|View full text |Cite
|
Sign up to set email alerts
|

The sixty‐year story of Finnish Bacillus Calmette‐Guérin (BCG) osteitis

Abstract: Aim A review published in 2015 showed that 331 Bacillus Calmette‐Guérin (BCG) osteitis cases were globally reported in 1976‐2012. The 222 Finnish cases from 1960 to 1988 formed two‐thirds of all cases. The present narrative review summarises epidemiological, clinical and immunological findings obtained from this Finnish cohort in relation to data from other countries. Methods Six reports including 93 BCG osteitis cases, which were not included in the 2015 review, were identified from PubMed. Results In all, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In a retrospective study from Taiwan not included in the systematic review covered the years 1998–2014, and the authors identified 70 BCG osteitis cases after newborn vaccination 2 . Globally, 424 BCG osteitis cases have ever been published 3 . As previously published, none of the patients of the present cohort died of tuberculosis, BCG infection or other severe infections, 13 which rules out severe deficiencies in host immunity.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a retrospective study from Taiwan not included in the systematic review covered the years 1998–2014, and the authors identified 70 BCG osteitis cases after newborn vaccination 2 . Globally, 424 BCG osteitis cases have ever been published 3 . As previously published, none of the patients of the present cohort died of tuberculosis, BCG infection or other severe infections, 13 which rules out severe deficiencies in host immunity.…”
Section: Discussionmentioning
confidence: 72%
“…Osteitis is a rare complication of Bacillus Calmette‐Guérin (BCG) vaccination and needs surgical intervention and an anti‐tuberculous treatment with drug combinations for 9 to 12 months 1,2 . Based on a recent review, over half of all 424 globally ever published BCG osteitis cases were diagnosed in Finnish children 3 . The crucial role of interferon‐gamma (IFN‐γ) in responses to mycobacteria, BCG included, has been known for a long time 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation